Evaluation of antimicrobial, hypotensive and diuretic effect of Eugenia uniflora extracts - Marinho de Souza, Joyce; Pimenta Rodrigues, Marcus Vinicius; Tardivo Cirqueira, Renata; Queiroz de Freitas Alves, Maria José; Peresi Lordelo, Eliana; Ferreira de Oliveira, Caio; Linhari Rodrigues Pietro, Rosemeire Cristina (O Mundo da Saúde, 2018)
The genus Eugenia sp. (Myrtaceae) comprises plants with reported antioxidant and antidiarrheal capability among other therapeutic potentials. The aim of this study was to evaluate the antimicrobial activity of essential oil; diuretic and hypotensive activities of aqueous extracts from leaves of Eugenia uniflora. The antimicrobial activity was evaluated . The diuretic and hypotensive activities were evaluated in normotensive Wistar rats by measuring blood pressure and urine flow after received four different concentrations of aqueous extracts (10%, 15%, 20% and 25%). Essential oil inhibited the growth of Candida parapsilosis and Candida albicans with MIC values lower than 14.41 mg/mL, equal to 57.75 mg/mL for Candida krusei. Among antibacterial effect, essential oil inhibited growth with a MIC equals to 153.93 mg/mL for all strains tested, except for Escherichia coli (MIC equals to 307.96 mg/mL. Aqueous extracts showed powerful reductions of the arterial pressure (34% and 31% lower than the control), after administration of 10% and 25% of aqueous extract, respectively. However, the animals that received the aqueous extract at the 15% and 20% concentrations presented a discrete hypotensive effect (20% and 21% lower than control group, respectively) concomitantly to powerful diuretic effect (280% and 91% higher than control group, respectively). These data confirmed the potential biological effect of this species, and represents an important step toward a depth study on the therapeutic properties of this species.